Analisa Gangguan Satu Fasa ke Tanah yang Mengakibatkan Sympathetic Trip pada Penyulang yang tidak Terganggu di PLN APJ Surabaya Selatan - Sentosa Setiadji, Julius; Machmudsyah, Tabrani; Kongdoro, Rusli (Institute of Research and Community Outreach, 2006)
Twenty kilovolts power distribution network system at East Java use high resistance (500 ?) grounding system that makes maximum single phase to ground fault current 25 Amperes. To detect this fault current, a Directional Ground Relay (DGR) is used. If a single phase to ground fault occurrs on Semolo feeder, then Gebanglor feeder and Srikana feeder which are supplied by the same bus with Semolo feeder (Nissin bus) will also trip (sympathetic trip). Sympathetic trip is caused by the total leakage current of arresters, transformers and low voltage panels on Gebanglor feeder dan Srikana feeder which is more than 2 Amperes (tap current setting of DGR is 2 Amperes). After maintenance, the total leakage current of the arresters on Gebanglor feeder is 0.046 Amperes and Srikana feeder is 0.026 Amperes. Abstract in Bahasa Indonesia : Sistem distribusi tenaga listrik 20 kV di Jawa Timur menggunakan sistem pentanahan dengan tahanan tinggi 500 Ohm sehingga arus gangguan satu fasa ke tanah maksimum adalah sebesar 25 Ampere. Untuk mendeteksi arus gangguan ini digunakan DGR (Directional Ground Relay). Apabila pada penyulang Semolo terjadi gangguan satu fasa ke tanah, maka penyulang Gebanglor dan Srikana yang dicatu dari bus yang sama dengan penyulang Semolo (bus Nissin) juga ikut trip (sympathetic trip). Penyebab terjadinya sympathetic trip adalah arus total kebocoran dari arrester, body trafo dan body panel TR GTT pada penyulang Gebanglor dan Srikana yang melebihi tap setting arus DGR sebesar 2 Ampere. Setelah dilakukan perbaikan, arus total kebocoran arrester pada penyulang Gebanglor menjadi sebesar 0.046 Ampere dan penyulang Srikana sebesar 0.026 Ampere. Kata kunci: penyulang, gangguan satu fasa ke tanah, sympathetic trip, dan directional ground relay.